ESTIMATING THE GOLD MINERALIZATION ZONE BY INDUCED POLARIZATION AND RESISTIVITY METHOD IN X VILLAGE, SUMATERA, INDONESIA - Andi, Andi; Hidayat, Nur; Praditya, Walhasbi; Prihatin, Rezal (Indonesian Physical Review, 2024)
This paper identifies the gold mineralization zone in X Village using the Induced Polarization and resistivity geoelectric method. The measurements were performed using the Wenner arrangement on six tracks, each separated by a distance of 235 meters and spaced 5 meters apart. The distribution of chargeability values was determined using the Induced Polarization method, while the distribution of resistivity values was determined using the resistivity geoelectric method at the research site. The identification results indicate that the suspected gold mineralization zone is on tracks 2 and 6. On track 2, the zone of suspected gold mineralization is suspected to be located 70-75 meters away from the starting point of measurement (point A). On track 6, it is located 65-75 meters away. The gold deposits are found in phyllite rocks that have undergone alteration, specifically philic, argillic, and silicified rock.